In vitro evaluation of nigella sativa-based colloidal drug carriers for delivery across blood-brain barrier - Nurul Hafizah binti Mohd Nor (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2015)
Nigella sativa (N. sativa) oil is known to have neuroregenerative effect while contributing to lipophilicity of either the formulation or of the therapeutic carrier system. The aim of this study was to evaluate the in vitro effect of Nigella sativa-based colloidal drug carriers for delivery across the blood-brain barrier. Firstly, the poly (D, L-lactic-co glycolic acid) (PLGA)/chitosan/N. sativa nanoparticles were fabricated via optimized diffusion-solvent-evaporation method and were characterized in terms of their particle size, charge analysis and surface morphology. From the characterization tests, five fabricated nanoparticles were selected according to the particle size in the range of 10 to 970 nm with smooth external surface and stable surface charge for further investigation. Secondly, the N. sativa oil-in-water microemulsions were prepared via the drop-wise titration of pre-determined volumes of N. sativa oil into mixtures of surfactant blends (Span 20, Span 80, Tween 20, Tween 80, Tween 85) and water. All transparent ternary mixtures were characterized for their viscosity, droplet size, thermodynamically stable characteristics, optically transparent appearance and high solubilization capability. The stability of the microemulsion was evaluated by subjecting them to stressful conditions, namely centrifugation (2000 g for 20 minutes) and heating in a dry oven (60 to 105 °C for 5 hours) and the droplet size was determined following one month storage at room temperature (25°C ± 2) thereafter. Based on the results, a phase ternary diagram was constructed from corresponding volumes of those 3 components. N. sativa mixtures (ranging from 7.4 to 10.7%) prepared at HLB 16 of surfactant blends (Tween 20:Tween 80; 6:4) with deionized water (ranging from 17.9 to 18.5%) yielded transparent liquids. The constructed phase diagram displayed regions of a few types of microemulsions and emulsions. The droplet size of freshly prepared mixtures was wider in range (5 to 15.6 nm) than the size following stressful condition (11.3 to 12.4 nm). The data indicated that N. sativa oil could be formulated into oil-in-water microemulsions at specific HLB value of surfactant blends. Following characterization of these two carrier systems, four in vitro testing were performed: (1) cell viability on MDCK 1 and N2a cells, (2) neurite outgrowth induction on N2a cells (3) transfection efficiency on MDCK 1 and N2a cells and (4) permeability assay across blood-brain barrier following loading of the nanoparticles. The results showed that: (1) no significant cell toxicity was found when MDCK 1 cells were treated with nanoparticles even at 1000 µg/ml. The microemulsions were concluded to be very potent to N2a cells and worked in a dose-dependent manner; (2) small particle size and high encapsulation efficiency of N. sativa oil could be related to the effect of the neuroregenerative property of N. sativa oil on N2a cells, leading to neurite outgrowth; (3) transfection efficiency assay indicated that the medium molecular weight of chitosan-bearing nanoparticle gave the highest transfection into the cells and (4) permeability assay showed the low molecular weight of chitosan-bearing nanoparticle gave the lowest transepithelial electrical resistance (TEER) value, indicated the highest permeation ability compared to the other nanoparticles. These systems were envisaged to enable rapid viewing of neurite extension on neuronal cell lines loaded with N. sativa oil. It was also suggested that N. sativa-based colloidal drug carrier would assist in future blood-brain barrier studies using non-viral gene therapy delivery system for neurodegenerative disease treatment.